2005
DOI: 10.4269/ajtmh.2005.73.74
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Indian Kala-Azar

Abstract: A case-control study was conducted to understand the risk factors associated with kala-azar in disease-endemic areas of Bihar, India. A total of 134 kala-azar cases treated at the Rajendra Memorial Research Institute of Medical Sciences in Patna and 406 healthy controls selected randomly from the neighborhoods of cases in their native villages were included in the study. Univariate analysis showed that education, a history of other diseases in the previous year, a history of kala-azar in the family, type of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 5 publications
11
89
3
1
Order By: Relevance
“…No patient was found in houses made of brick wall and concrete floor (Table 5). Ranjan et al (2005) showed in a study that the use of mud for wall construction or for plastering walls was found to be significantly associated with kala-azar. In Fulbaria, total 94 patients out of 97 kala-azar patients had cattle shed in their houses and the prevalence was 96.91%.…”
Section: Resultsmentioning
confidence: 99%
“…No patient was found in houses made of brick wall and concrete floor (Table 5). Ranjan et al (2005) showed in a study that the use of mud for wall construction or for plastering walls was found to be significantly associated with kala-azar. In Fulbaria, total 94 patients out of 97 kala-azar patients had cattle shed in their houses and the prevalence was 96.91%.…”
Section: Resultsmentioning
confidence: 99%
“…Trees and plantations around the houses have been treated as a significant factor of Kala azar. According to Ranjan et al 28 , some trees are considered source of fructose for Phlebotomine sandflies and also produce dark and damp environments around the peripheral neighborhood, the ideal places of shelter for the mosquito.…”
Section: Discussionmentioning
confidence: 99%
“…In these locations, the disease follows an endemic behavior and may, eventually, even acquire epidemiologic status (Costa: unpublished data). Several studies have pointed, in detail, to a series of risk factors associated mainly to local socioeconomic conditions, which may determine the occurrence of L. (L.) chagasi in canine and human population, like precarious housing conditions that promote the development of the vector [31][32][33][34][35] , apart from the lack of elementary sanitation and the sporadic garbage collection, which furnish the ideal microenvironments for phlebotomine reproduction 5,36 . These risk factors were observed in all regions evaluated in the present study.…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%